Project control : integrating cost and schedule in construction - DelPico, Wayne J. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
4 The Schedule; Basic Scheduling Concepts; Types of Schedules; The Checklist; The Schedule Board; The Bar Chart; The Look Ahead; The Linear Schedule; Advanced Scheduling Methods; Program Evaluation and Review Technique; Critical Path Method (CPM); The CPM Schedule as a Management Tool; Tasks; The Work Breakdown Structure; Task Types; Task Descriptions; Task Durations; Interdependencies; Complex Relationships-Lags and Leads; Milestones and Constraints; Float; Updating the Schedule; Summary; 5 The Budget; Fundamentals of the Estimating Process; Types of Estimates.
Reasons and methodologies for proper planning, monitoring, and controlling construction project costs and schedule The key to successful construction project control is the fusing of cost to schedule, enabling the management of one to help the management of the other. This requires that a task's cost and its duration have a direct relationship, not an arbitrary assignment by the scheduler. Ensuring that relationship is correct and setting the appropriate baseline for tracking is the domain of the project control analyst. Written by a seasoned professional in the field, Pro.
The Basics -- Introduction to Project Control -- Pre-Construction Planning -- The Schedule -- The Budget -- Integrating the Schedule and the Budget -- Calculating and Analyzing Progress -- Analyzing & Reporting Variances in Schedule and Cost -- Recognizing Trends and Forecasting Performance -- Productivity -- Acceleration and Schedule Compression -- Resource Management -- Risk Management -- Project Closeout.
"Published simultaneously in Canada"--Title page verso.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Construction projects -- Management; Building -- Estimates; Scheduling; Building -- Estimates; Construction projects -- Management; Scheduling; TECHNOLOGY & ENGINEERING -- Civil -- General; Electronic books; Electronic books; Electronic books